Pravopisna razpotja Razprave o pravopisnih vprašanjih - Dobrovoljc, Helena; Lengar Verovnik, Tina (ZRC SAZU, Založba ZRC, 2015)
The purpose of the monograph Crossroads of Orthography which aims, as did its predecessor Junctures of Orthography (2012), to present arguments for additions and changes to normative rules - is to encourage normative and orthographic activities in Slovenian linguistic society. In the 20th century, these activities were intensified only after publication of normative guides called "pravopis" and during polemical discussions that accompanied the results. With both monographs, we want to encourage public debate before the publication of the new normative guide and also to find answers to the language and normative difficulties, which are not problematic only in terms of linguistics and orthography, but also within the wider social environment. In six thematic sections of the monograph, 26 authors of 22 articles deal with specific normative issues (capitalization and punctuation) as well as with other topics on different levels of grammatical description - phonology, morphology and word formation. The problems of orthography in other, often non-linguistic fields are discussed. In the last two parts of the monograph, the problems of lexicographic approaches to orthography and its relation to language culture are considered.